2019
DOI: 10.1111/myc.12910
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world use—Isavuconazole at a large academic medical center

Abstract: Summary Background Isavuconazole use in the real‐world setting has not been extensively described. Subgroups of patients with particular prognostic significance, such as previous triazole prophylaxis or treatment and the important subgroup treated empirically for invasive fungal infection, have beforehand been excluded from trials. Objectives We aimed to determine treatment response and safety in these patients at a large US transplant and cancer centre. Patients/Methods We conducted a retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
4
20
1
3
Order By: Relevance
“…Adverse events to ISZ in the present study were mostly gastroenteric and hepatic, reported by the treating physician and also reported by others [ 12 , 14 , 25 , 29 , 30 , 31 ]. Adverse events were not closely related to high median TDMs.…”
Section: Discussionsupporting
confidence: 89%
“…Adverse events to ISZ in the present study were mostly gastroenteric and hepatic, reported by the treating physician and also reported by others [ 12 , 14 , 25 , 29 , 30 , 31 ]. Adverse events were not closely related to high median TDMs.…”
Section: Discussionsupporting
confidence: 89%
“…Another study evaluated isavuconazole prophylaxis in lung transplant recipients and identified a 3.5% bIFD rate among 144 patients 6 . So far, the highest reported bIFD incidence is 13.0% in 100 leukemia patients 13 and the lowest is 0% in 11 solid organ transplants, 15 HSCT, and 58 acute leukemia patients receiving isavuconazole for either prophylaxis or treatment 7,13 . Our overall 8.5% breakthrough rate is most similar to a study by Fontana et al, who reported an 8.3% bIFI rate among 145 allogeneic HSCT patients receiving isavuconazole for primary prophylaxis 5 .…”
Section: Discussionsupporting
confidence: 85%
“…Our results show that the most common reasons for switching to isavuconazole was better tolerability compared to first‐line agents. Similar to a study published by Hassouna et al, a majority of our patients were switched to isavuconazole for its beneficial effect on QTc, broad spectrum of activity, high oral bioavailability, lower incidence of hepatotoxicity, and to avoid drug‐drug interactions 7 . Owing to isavuconazole's unique ability to inhibit L‐type calcium channels, all patients who switched for prolonged QTc experienced shortening effects 10 .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations